问题 解答题
分式方程:
(1)
x
2x-3
+
5
3-2x
=4

(2)
6
x2-1
-1=
3
x-1

(3)
1-x
x-2
+2=
1
x-2

(4)
x
x-1
+
1
x
=1      
(5)
x-3
x-2
+1=
3
2-x

(6)
x
x+1
=
2x
3x+3
+1
答案

(1)去分母得:x-5=4(2x-3),

去括号得:x-5=8x-12,

移项合并得:-7x=-7,

解得:x=1,

经检验x=1是原分式方程的解;

(2)去分母得:6-(x2-1)=3(x+1),

整理得:x2+3x-4=0,即(x-1)(x+4)=0,

解得:x=1或x=-4,

经检验x=1是增根,

则原分式方程的解为x=-4;

(3)去分母得:1-x+2(x-2)=1,

去括号得:1-x+2x-4=1,

移项合并得:x=4,

经检验x=4是原分式方程的解;

(4)去分母得:x2+x-1=x(x-1),

去括号合并得:2x=1,

解得:x=

1
2

经检验x=

1
2
是原分式方程的解;

(5)去分母得:x-3+x-2=-3,

移项合并得:2x=2,

解得:x=1,

经检验x=1是原分式方程的解;

(6)去分母得:3x=2x+3(x+1),

去括号得:3x=2x+3x+3,

移项合并得:2x=-3,

解得:x=-

3
2

经检验x=-

3
2
是原分式方程的解.

补全对话,情景问答
单项选择题